Ecological factors and childhood eating behaviours at 5 years of age: findings from the ROLO longitudinal birth cohort study - Anna Delahunt; Marie C. Conway; Eileen C. O'Brien; Aisling A. Geraghty; Linda M. O'Keeffe; Sharleen L. O'Reilly; Ciara M. McDonnell; Patricia M. Kearney; John Mehegan; Fionnuala M. McAuliffe (BMC, 2022)
Abstract Background Individual differences in children eating behaviours have been linked with childhood overweight and obesity. The determinants of childhood eating behaviours are influenced by a complex combination of hereditary and ecological factors. This study examines if key ecological predictors of childhood overweight; maternal socio-economic status (SES), children's screen time, and childcare arrangements, are associated with eating behaviours in children aged 5-years-old. Methods This is secondary, cross-sectional analysis of the ROLO (Randomized COntrol Trial of LOw glycemic diet in pregnancy) study, using data from the 5-year follow-up (n = 306). Weight, height, and body mass index (BMI) were obtained from mothers and children at the 5-year follow-up. Children's BMI z-scores were calculated. SES was determined using maternal education level and neighborhood deprivation score. Information on children's screen time and childcare arrangements were collected using lifestyle questionnaires. Children's eating behaviours were measured using the Children's Eating Behaviour Questionnaire (CEBQ). Multiple linear regression, adjusted for potential confounders, assessed associations between maternal SES, screen time and children's eating behaviours. One-way ANOVA, independent sample t-tests and Spearman's correlation examined childcare exposure and children's eating behaviour. Results Mothers in the lowest SES group had higher BMI and were younger than those in the highest SES group (p =  < 0.001, p = 0.03 respectively). In adjusted analysis, the lowest SES group was associated with a 0.463-point higher mean score for 'Desire to Drink' (95% CI = 0.054,0.870, p = 0.027) and higher 'Slowness to Eat' (B = 0.388, 95% CI = 0.044,0.733, p = 0.027) when compared with the highest SES group. Screen time (hours) was associated with higher 'Food Fussiness' (B = 0.032, 95% CI = 0.014,0.051, p = 0.001). Those who attended childcare had higher scores for 'Desire to Drink'(p = 0.046). No relationship was observed between longer duration (years) spent in childcare and eating behaviours. Conclusions In this cohort, the ecological factors examined had an influence on children's eating behaviours aged 5-years-old. Our results illustrate the complexity of the relationship between the child's environment, eating behaviour and children's body composition. Being aware of the ecological factors that impact the development of eating behaviours, in the pre-school years is vital to promote optimal childhood appetitive traits, thus reducing the risk of issues with excess adiposity long-term.